Beneficial mutualistic fungus Suillus luteus provided excellent buffering insurance in Scots pine defense responses under pathogen challenge at transcriptome level - Zilan Wen; Minna J. Manninen; Fred O. Asiegbu (BMC Plant Biology)
Abstract Background Mutualistic mycorrhiza fungi that live in symbiosis with plants facilitates nutrient and water acquisition, improving tree growth and performance. In this study, we evaluated the potential of mutualistic fungal inoculation to improve the growth and disease resistance of Scots pine (Pinus sylvestris L.) against the forest pathogen Heterobasidion annosum. Results In co-inoculation experiment, Scots pine seedlings were pre-inoculated with mutualistic beneficial fungus (Suillus luteus) prior to H. annosum infection. The result revealed that inoculation with beneficial fungus promoted plant root growth. Transcriptome analyses revealed that co-inoculated plants and plants inoculated with beneficial fungus shared some similarities in defense gene responses. However, pathogen infection alone had unique sets of genes encoding pathogenesis-related (PR) proteins, phenylpropanoid pathway/lignin biosynthesis, flavonoid biosynthesis, chalcone/stilbene biosynthesis, ethylene signaling pathway, JA signaling pathway, cell remodeling and growth, transporters, and fungal recognition. On the other hand, beneficial fungus inoculation repressed the expression of PR proteins, and other defense-related genes such as laccases, chalcone/stilbene synthases, terpene synthases, cytochrome P450s. The co-inoculated plants did not equally enhance the induction of PR genes, chalcone/stilbene biosynthesis, however genes related to cell wall growth, water and nutrient transporters, phenylpropanoid/lignin biosynthesis/flavonoid biosynthesis, and hormone signaling were induced. Conclusion S. luteus promoted mutualistic interaction by suppressing plant defense responses. Pre-inoculation of Scots pine seedlings with beneficial fungus S. luteus prior to pathogen challenge promoted primary root growth, as well as had a balancing buffering role in plant defense responses and cell growth at transcriptome level.